Scholarly publishing in sub-Saharan Africa in the twenty-first century: challenges and opportunities. - Ondari, Ezra Okemwa (My University, 2007)
A free flow of ideas and information is vital to the process of scientific inquiry, and in turn to the ability to address economic, environmental and social development issues both in the sub-Saharan Africa region and globally. Most of the challenges facing scholarly publishing in sub-Saharan Africa are global and do not respect national boundaries. Scholarly publishing enables research findings of scholars to cross international boundaries to provide strong, positive connections between individual scholars, institutions and nations. Such exchanges contribute to the expansion of the global knowledge base to which the sub-Saharan Africa region is linked. Participation in the global arena through scholarly communication may enable the sub-Saharan Africa region to have access to knowledge and information it needs to succeed in the global economy that is being digitized rapidly. Scholarly publishing is as a result of research and innovation which may improve the quality of knowledge and information produced by scholars in the sub-Saharan Africa region. This paper explores the challenges and opportunities of scholarly publishing in sub-Saharan Africa in the twenty-first century. The paper also proposes ways of capitalising on the vast opportunities of enhancing knowledge production and dissemination in sub-Saharan Africa through scholarly publishing in the twenty-first century. An analysis of publication records of subSaharan Africa between 1997 and 2007 in the Thompson Scientific was conducted. There are many challenges confronting scholarly publishing in sub-Saharan Africa. The challenges include technological, socio-political, economic and environmental. The 21st century brings with it opportunities that may enhance sub-Saharan Africa’s visibility of scholarly publishing.